Pharmacovigilance strategy: opportunities for cross-national learning - Irene Fermont (BMC, 2019)
Abstract The Israeli Ministry of Health has set up the foundations of a National Pharmacovigilance System. The next step is to adopt the best of the international ideas, trends and approaches which are shaping the future of pharmacovigilance. Specifically: 1) The risk management approach requires proactively preventing or minimizing risks, starting in early clinical development and extending all along the lifecycle of a pharmaceutical. 2) Drug safety is a multidisciplinary discipline where all stakeholders should be involved. 3) Clinical trials provide an ideal safety profile limited to the restrictive conditions of the trial. Only real-world data, from the post marketing period, will reveal the real risk/benefit balance for the use of a pharmaceutical in regular clinical care. 4) Artificial intelligence is needed to analyze the large amount of data collected through the post-marketing studies, electronic medical records and the internet. Many AI tools have been developed to support better use of pharmaceuticals. 5) Quality-oriented, thorough inspections and audits are critical for achieving patient safety. 6) Patients should be recognized as active players in their treatment who can, and should, have access to safety information through the major agencies' websites. Israel can benefit from several of its key assets to reach a higher level of pharmacovigilance: 1) Israel's four HMOs are organized in a way that allows them to have quick and efficient dialogue with healthcare professionals and with patients. Moreover, a new project named, Big Data in Health, will pool the epidemiologic databases of the HMOs, providing precious information for understanding risk factors, detecting alerts, and developing personalized medicine. 2) Formal risk management activities have long been part of the culture of hospitals and should be applied increasingly to ensuring drug safety. Israel has the organizational, scientific, technological and cultural resources needed to quickly overcome the challenges and go beyond its current state to build a unique pharmacovigilance system which could serve as an example for other countries.